Chitosan/Graphene Oxide Composite as an Effective Adsorbent for Reactive Red Dye Removal. (1st July 2016) - Guo, Xiaoqing; Qu, Lijun; Tian, Mingwei; Zhu, Shifeng; Zhang, Xiansheng; Tang, Xiaoning; Sun, Kaikai
ABSTRACT: : Chitosan, modified with different dosages of graphene oxide (GO) and reduced graphene oxide (rGO), was first prepared, and its adsorption capacity for reactive red (RR) dye in aqueous solutions was investigated, in this paper. The structure and morphology of the adsorbents were characterized by FT‐IR, XRD, SEM, EDX, BET, and TGA. The effect of varying parameters (pH, temperature, adsorbent loading, and contact time) was also investigated. The maximum adsorption capacity based on the Langmuir model was found to be 32.16 mg/g. In addition, experimental kinetic data were analyzed by the psuedo‐first order and psuedo‐second order equation models. The psuedo‐second order model proved to be the best model for the adsorption system, which suggested that adsorption might be controlled by the chemical rate‐limiting step through sharing of electrons or by covalent forces.